Probability analysis of rainfall for agricultural planning at Chhura tehsil of Gariyaband district of Chhattisgarh plain - DEO, RAJENDRA; SINHA, B.L.; SINHA, JITENDRA (Journal of Soil and Water Conservation, 2023)
Rainfall probability analysis provides a better opportunity to forecast the least guaranteed rainfall to aid in crop planning. Based on data collected over a 30-year period (1990–2020) from the Chhura tehsil of the Gariyaband district, Chhattisgarh, an attempt has been made to examine the patterns of rainfall distribution, including weekly, seasonal, and annual rainfall. Using the Weibull plotting tool, expected weekly, monthly, seasonal, and yearly rainfall values were calculated for various probability levels. Based on a 30-year yearly average, the research shows that 1208.8 mm of rain were actually seen, coming off of an average of 67.5 rainy days. At a 75% probability level, 942.5 mm of yearly precipitation is predicted. Similar to the above, at a 75% chance level, the maximum weekly rainfall of 111.8 mm was expected to occur in the 29th week, followed by 105.6 mm in the 27th standard week, and the lowest rainfall of 0.0 mm in the 40th week. While analysis of monthly rainfall at 70, 75, and 80% probability levels reveals that July, August, and September are the three crucial wet months with odds of obtaining a monthly rainfall between 100 and 150 mm. At a 70% probability level, the seasonal rainfall prediction for the Kharif season shows 1090.1 mm.